Effectiveness of Tuberculosis Control by Including Dots in the Scope of Work of Tamalanrea Puskesmas of 2010 - Idrus, Hasta H; Mangarengi, Yusriani (Sari Mutiara Indonesia University Press, 2018)
Background: It is estimated that about one-third of the world's population has been affected by Mycobacterium tuberculosis.In 1995, an estimated 9 million new TB patients and 3 million TB deaths worldwide, an estimated 95% of TB cases and 98% of TB deaths occur worldwide and the death of women due to TB more than death, childbirth and nifes, major TB problems (high burden countries.) In response, in 1993, WHO launched TB as a global emergency, Objective: To know effectiveness of Tuberculosis control with DOTS strategy based on Proportion of Pulmonary TB BTA Positive patient between Suspect at Tamalanrea Health Center. Method: This research is a survey research with descriptive approach that aims to describe data based on existing facts. The data consisting of these results is further illustrated by the purpose of the study leads. Results: The results showed a median success rate of 81%, under the target of at least 85%. In 3 villages, the success rate of treatment reaches 100%, ie in Tamalanrea, Kapasa, Parangloe urban village. And contains 2 kelurahan that the success rate of treatment under the target is on the village Tamalanrea Jaya and Bira